Study on current status of water quality and heavy metals around Tasik Chini - Che Abdul Hafiz, Che Yahya (2018)
The purpose of this research is to analyse water quality at Tasik Chini in 2017. A total of fourteen water quality parameters and five heavy metals concentration were measured based on Malaysian Department of Environment Water Quality Index (DOE-WQI) and also classified according to the Interim National Water Quality Standard, Malaysia (INWQS). The physical and chemical variable such as pH, Electrical Conductivity (EC), Turbidity, Temperature, Dissolved Oxygen (DO), Total Suspended Solid (TSS), Suspended Solid (SS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (NH3-N), Hardness, Nitrate (NO3-) Potassium (K), Phosphorus (P) was analyse through in-situ and laboratory experiments. Five parameters of heavy metals concentration to be identified are Cadmium (Cd), Copper (Cu), Chromium (Cr), Nickel (Ni) and Lead (Pb) were tested by using Atomic Absorption Spectroscopy (AAS). Result shown based on Malaysian WQI, the water from most of the selected rivers in Tasik Chini is classified as Class III, where the water required extensive treatment. Based on result collected, illegal logging, iron mining and agriculture activities have taken place in surrounding of the lake consequently affected the pollution of water at Tasik Chini.